2017
DOI: 10.1111/hepr.13000
|View full text |Cite
|
Sign up to set email alerts
|

Loss of skeletal muscle mass in patients with chronic liver disease is related to decrease in bone mineral density and exercise tolerance

Abstract: Skeletal muscle reduction in chronic liver disease is closely related to exercise tolerance and osteoporosis, and these factors are believed to be associated with physical inactivity in daily life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 65 publications
(115 reference statements)
1
4
0
Order By: Relevance
“…Improving exercise habits through scientific exercise can improve exercise ability and cardiorespiratory health, which is accompanied by improvements in body composition and bone density. Moreover, the relationship between body composition and bone density to exercise ability and cardiorespiratory health can also be reflected in some people with diseases [19][20][21]. The above results are consistent with our research: the slope S reflected the exercise ability at a specific heart rate, which was capable of evaluating a person's cardiorespiratory fitness (aerobic capacity).…”
Section: Discussionsupporting
confidence: 89%
“…Improving exercise habits through scientific exercise can improve exercise ability and cardiorespiratory health, which is accompanied by improvements in body composition and bone density. Moreover, the relationship between body composition and bone density to exercise ability and cardiorespiratory health can also be reflected in some people with diseases [19][20][21]. The above results are consistent with our research: the slope S reflected the exercise ability at a specific heart rate, which was capable of evaluating a person's cardiorespiratory fitness (aerobic capacity).…”
Section: Discussionsupporting
confidence: 89%
“…Chronic kidney disease was identified in 22 patients (20%) and diabetes mellitus in 25 patients (22%). The median handgrip strength was 32 (29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40) kg in men and 21 (17)(18)(19)(20)(21)(22)(23)(24)(25) kg in women. The median interval period between measurements of the ASMI and BMD was 35 (0-91) days.…”
Section: Baseline Characteristicsmentioning
confidence: 98%
“…[14][15][16] Although handgrip strength and low lean body mass measured by dual-energy X-ray absorptiometry (DEXA) are associated with low BMD in LC patients, the association between sarcopenia and osteoporosis in patients with CLD remains unclear. 17,18 The aim of this study was to investigate the relationship between sarcopenia and osteoporosis in patients with CLD.…”
Section: Introductionmentioning
confidence: 99%
“…The bibliographies of relevant studies were also searched, and 2 additional studies [24,25] were identified to be eligible. Ultimately, 56 studies [6–14,21,24–69] involving 796,914 participants were included. Of these, 38 studies [6,9–11,13,21,25,27–29,31–33,35,37–39,41–43,45,47–49,51,52,54–56,58,59,61–63,65–68] comprising 50 independent studies examined the contribution of sarcopenia to osteoporosis, 17 studies [6–8,12,14,24,26,30,34,36,44,50,52,53,57,64,69] with 405,847 participants examined the contribution of osteoporosis to sarcopenia, and 5 studies [61–65] comprising 7 independent studies with 171,514 participants examined the decrease in osteoporosis risk for each standard deviation (SD) increase in relative appendicular skeletal muscle mass (RASM) (Fig.…”
Section: Resultsmentioning
confidence: 99%